2005
DOI: 10.1097/01.prs.0000156918.15595.85
|View full text |Cite
|
Sign up to set email alerts
|

Sternal Wound Reconstruction with Transverse Plate Fixation

Abstract: Transverse plate fixation of the sternum in conjunction with simple bilateral pectoralis advancement flaps is a safe and effective means of treating complicated sternal wounds. The benefits of this procedure over standard muscle flap reconstruction include earlier extubation, a tension-free repair with faster and more reliable healing, and a simpler flap technique without the need for turning the pectoral muscle over or dividing it from its origin. The authors believe that this technique is safe and easy to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 14 publications
1
69
0
1
Order By: Relevance
“…Treatment modalities of DSWI have evolved as well during these years in our tertiary centre, from debridement with open packing and drainage to close irrigation with primary rewiring, followed by the introduction of pectoralis myocutaneous flaps (PMFs). Vacuum-assisted therapy (VAC) as a first-line of treatment [2] (KCI W ) with delayed sternal osteosynthesis with horizontal titanium plate fixation (Synthes W ) covered with PMF flaps has recently been proposed to improve clinical results and to deal with complex sternal infections and multiple sternal fractures [3]. The objective of this study was to analyse the early clinical results and mid-term impact on survival for patients managed with these newly introduced treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment modalities of DSWI have evolved as well during these years in our tertiary centre, from debridement with open packing and drainage to close irrigation with primary rewiring, followed by the introduction of pectoralis myocutaneous flaps (PMFs). Vacuum-assisted therapy (VAC) as a first-line of treatment [2] (KCI W ) with delayed sternal osteosynthesis with horizontal titanium plate fixation (Synthes W ) covered with PMF flaps has recently been proposed to improve clinical results and to deal with complex sternal infections and multiple sternal fractures [3]. The objective of this study was to analyse the early clinical results and mid-term impact on survival for patients managed with these newly introduced treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…3 Many authors proposed this technique for sternal reconstruction after complicated median sternotomy. 4,5 For traumatic manubriosternal dislocation, the rigid plate osteosynthesis allows a reduced rate of iatrogenic complications and shortened hospitalization because it is an easy method to perform and the immediate clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently, sternal wound reconstructions with wire or a plate after median sternotomy have been reported. Kiessling et al 5 reported a double-wire technique for obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cicilioni et al 6 reported a transverse titanium plate fi xation technique. All patients who underwent the procedure during primary and secondary operations were included in their study.…”
Section: Discussionmentioning
confidence: 99%